TRANSLATION ISSUES OF MEDICAL TERMINOLOGY: THE CASE OF UZBEK-ENGLISH LANGUAGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
As society, science, culture, and information technology advance, massive changes are occurring in all language reserves. After all, innovation in all domains begins with the language's lexical system, articulated through terms. As the medical industry, like other fields, evolves at a quick pace, the demand for medical language grows. This article discusses medical terms and terminology in world linguistics. It is devoted to translation problems of medical terms in English and Uzbek.